Role of Ayurveda Treatment to Manage Hypothyroidism: An Experience - Ajay; Varsakiya, Jitendra (International Research Journal of Ayurveda & Yoga, 2025)
Hypothyroidism constitutes a hypometabolic clinical condition characterized by the insufficient synthesis of thyroid hormones over an extended duration. Approximately one in ten adults in India is affected by hypothyroidism. The prevalence among women is sixfold greater than that in men. Clinical manifestations of hypothyroidism range from life-threatening to no signs or symptoms. The most common symptoms in adults are fatigue, lethargy, cold intolerance, weight gain, constipation, change in voice, and dry skin, but clinical presentation can differ with age and sex, among other factors. The foundational principles of Ayurvedic pathogenesis suggest that the primary contributing factor is the diminished functionality of Agni, commonly termed Agnimandya. Here is the case of a 32-year-old female patient having a 5-month history of hypothyroidism who sought treatment at our hospital. She was prescribed an Ayurvedic regimen consisting of Virechan karma was done with Erand tailam, Pathyadi kwath, and Avipattikar churna. After Virechan karma follow-up with Ashwagandha churna 3 g twice a day, Chitrakadi Vati 1 tablet twice a day after a meal, and Triphala Churna 5 g at bedtime. The findings suggested the possibility of Ayurvedic treatments for endocrine problems and showed a good effect on the management of hypothyroidism.